Azo-aromatic functionalized polyethylene by nitroxide radical coupling (NRC) reaction: Preparation and photo-physical properties. (15th January 2016) - Cicogna, Francesca; Domenichelli, Ilaria; Coiai, Serena; Bellina, Fabio; Lessi, Marco; Spiniello, Roberto; Passaglia, Elisa
Abstract: The nitroxide radical coupling (NRC) reaction between the 4-(phenylazo)-benzoyl-2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical (AzO-TEMPO) or the 4-(2-thienylazo)-benzoyl-2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical (ThiO-TEMPO) and polyethylene macroradicals allowed the preparation of "functional" polyolefins bearing covalently grafted azo-aromatic chromophores. A comparison of the photo-physical behavior of the free and grafted RO-TEMPO molecules was carried out by UV-Vis spectroscopy irradiating the free RO-TEMPO solutions and the functionalized polymer films at 366 and 254 nm. Results evidenced the transfer of the photo-physical properties of the chromophores to the polymer matrix. Interestingly, some different isomerization abilities and kinetics between the free and grafted RO-TEMPO moieties, depending on the nature of the aromatic group bonded to the diazo-moiety and on the structure of the polymer matrix, were observed. Indeed, when the chromophores were grafted to the polymer, the isomerization resulted to be less efficient in terms of photo-isomerization degree and isomerization rate than in solution, suggesting a strong effect of the semi-crystalline matrix especially in the case of the more rigid HDPE. Finally the determination of the water contact angle of the functionalized polymers, before and after photo-isomerization, confirmed the occurrence of the isomerization and evidenced an increase of the wettability of the polymer surface owing to the process. Graphical abstract: Highlights: NRC reaction as a tool to graft photo-isomerizable chromophore to polyolefins (PO). Isomerization of free and grafted azo-aromatic TEMPO by 366 and 254 nm irradiation. NRC reaction as a tool to transfer the properties of functional TEMPO to PO. Matrix effect on the isomerization kinetic of azo aromatic TEMPO grafted to PO. Surface wettability changes upon irradiation of azo-aromatic TEMPO functionalized PO.